2004
DOI: 10.1210/jc.2003-032049
|View full text |Cite|
|
Sign up to set email alerts
|

The Cardiovascular Risk of Young Women with Polycystic Ovary Syndrome: An Observational, Analytical, Prospective Case-Control Study

Abstract: To evaluate the cardiovascular risk of polycystic ovary syndrome (PCOS), we investigated lipid profile, metabolic pattern, and echocardiography in 30 young women with PCOS and 30 healthy age- and body mass index (BMI)-matched women. PCOS women had higher fasting glucose and insulin levels, homeostasis model assessment score of insulin sensitivity, total cholesterol (TC) and low density lipoprotein cholesterol (LDL-C) levels, and TC/high density lipoprotein cholesterol (HDL-C) ratio and lower HDL-C levels than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
187
2
15

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(213 citation statements)
references
References 62 publications
9
187
2
15
Order By: Relevance
“…While several studies have shown that women with PCOS are more prone to atherosclerotic issues, [16][17][18][19][20]37 we show here, as Mak and Dokras 22 suggested, that women with PCOS have a higher probability of having VTE compared with women without PCOS. 22 We acknowledge that our findings should be interpreted with caution and the relationship between PCOS and VTE should be evaluated further in prospective studies because our data were obtained from administrative data.…”
Section: Author Manuscriptsupporting
confidence: 58%
See 2 more Smart Citations
“…While several studies have shown that women with PCOS are more prone to atherosclerotic issues, [16][17][18][19][20]37 we show here, as Mak and Dokras 22 suggested, that women with PCOS have a higher probability of having VTE compared with women without PCOS. 22 We acknowledge that our findings should be interpreted with caution and the relationship between PCOS and VTE should be evaluated further in prospective studies because our data were obtained from administrative data.…”
Section: Author Manuscriptsupporting
confidence: 58%
“…These findings also demonstrate the complex nature of PCOS and its related clinical consequences. For instance, increased cardiovascular risks has been found among women with phenotype A (hyperandrogenism and ovulatory dysfunction) or classic PCOS [15][16][17][18][19][20] ; on the other hand, Wiltgen and Spritzer 30 showed that hirsute ovulatory patients with polycystic ovaries (phenotype B) had a lower prevalence of cardiovascular risk factors than those with the classic PCOS phenotype. One would then expect that the highest probability of VTE also would be found among women with phenotype A and the lowest probability among women with phenotype B.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Infatti, diverse evidenze mostrano una relazione tra malattia cardiaca e PCOS e rischio CV, cioè dislipidemia [49], insulino-resistenza (50), LVM (massa ventricolare sinistra) aumentata [51] e disfunzione diastolica del ventricolo sinistro [51,19].…”
Section: Struttura E Funzione Cardiaca Nella Pcosunclassified
“…Thus, insulin resistance may develop in parallel with androgen excess, rather than independently of it. The known association of PCOS with insulin resistance [57] and obesity accounts for the predisposition of these women to metabolic syndrome [58,59] and type 2 diabetes mellitus (T2DM) [60,61]. The authors' preliminary studies show a stronger relationship of adolescent PCOS to parental metabolic syndrome than to any other parental feature [62].…”
Section: Etiology Of Polycystic Ovary Syndromementioning
confidence: 99%